Heavy drinking and problem drinking among youth in Uganda: A structural equation model of alcohol marketing, advertisement perceptions and social norms. (27th June 2022) - Swahn, Monica H.; Culbreth, Rachel; Fodeman, Ari; Cottrell‐Daniels, Cherell; Tumwesigye, Nazarius Mbona; Jernigan, David H.; Kasirye, Rogers; Obot, Isidore
Abstract: Introduction: To determine the role of alcohol marketing, perceptions of marketing and social norms on heavy alcohol use and problem drinking among vulnerable youth in Uganda. Methods: The Kampala Youth Survey is a cross‐sectional study conducted in 2014 with service‐seeking youth (ages 12–18 years) living in the slums of Kampala ( n  = 1134) who were participating in Uganda Youth Development Link drop‐in centres. Survey measures assessed perceptions of alcohol advertisements, social norms regarding alcohol use, heavy alcohol use and problem drinking. Factor analyses and structural equation models were computed to determine the predictors (e.g. social norms and alcohol marketing exposure) for drinking amounts, heavy drinking and problem drinking. Results: Alcohol marketing allure, perceptions of adults' alcohol attitudes and respondent's male gender were significantly predictive of heavy drinking. Similarly, in addition to drinking amount and heaviness, only alcohol marketing exposure and friends' alcohol attitudes, as well as respondent's own attitudes about alcohol, significantly predicted variation in problem drinking. Discussion and Conclusions: Alcohol marketing exposure and allure are significant predictors of heavy drinking and problem drinking among youth in Uganda. Prevention programs that reduce exposure to and allure of alcohol marketing may prove promising for reducing alcohol use and related problems among these vulnerable youth in a low‐resource setting.